2017
DOI: 10.3389/fped.2017.00101
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy in Pediatric Hypertension: A Mini Review

Abstract: Adults with arterial hypertension (HTN) have stroke, myocardial infarction, end-stage renal disease (ESRD), or die at higher rates than those without. In children, HTN leads to target organ damage, which includes kidney, brain, eye, blood vessels, and heart, which precedes “hard outcomes” observed in adults. Left ventricular hypertrophy (LVH) or an anatomic and pathologic increase in left ventricular mass (LVM) in response to the HTN is a pediatric surrogate marker for HTN-induced morbidity and mortality in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 79 publications
(90 reference statements)
0
24
0
1
Order By: Relevance
“…LVH is a frequent finding in pediatric RT recipients ranging from 56% to 82%, but the definition of LVH varied between studies . Our study demonstrated that the prevalence of LVH after RT was 76.7% (23/30 patients), by using the definition from recently updated AAP guideline .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…LVH is a frequent finding in pediatric RT recipients ranging from 56% to 82%, but the definition of LVH varied between studies . Our study demonstrated that the prevalence of LVH after RT was 76.7% (23/30 patients), by using the definition from recently updated AAP guideline .…”
Section: Discussionmentioning
confidence: 60%
“…LVH has been used as an early surrogate outcome for cardiovascular risk in pediatric population . Consequently, adequate blood pressure control results in reduction of LVH prevalence and decreased LVMI …”
Section: Introductionmentioning
confidence: 99%
“…Woroniecki and colleagues’ article on left ventricular hypertrophy (LVH) in pediatric hypertension (HTN) reviewed current definitions, clinically relevant methods of LVM measurements, and normalization methods as well as its epidemiology, management, and reversibility in children with HTN (1). …”
mentioning
confidence: 99%
“…Woroniecki and colleagues’ article (1) exposed the puzzling concern of defining LVH in a pediatric population on the basis of the existence of diverse criteria with pros and cons. These arguments are not new and have contributed to the difficulty in recent years to ascertain a reliable standardization of LVH definition at the early stages of life in children and adolescents suffering from HTN.…”
mentioning
confidence: 99%
See 1 more Smart Citation